CDKL5/STK9 is mutated in Rett syndrome variant with infantile spasms. Issue 2 (2nd February 2005) - Scala, E; Ariani, F; Mari, F; Caselli, R; Pescucci, C; Longo, I; Meloni, I; Giachino, D; Bruttini, M; Hayek, G; Zappella, M; Renieri, A
Abstract : Background: Rett syndrome is a severe neurodevelopmental disorder, almost exclusively affecting females and characterised by a wide spectrum of clinical manifestations. Both the classic form and preserved speech variant of Rett syndrome are due to mutations in the MECP2 gene. Several other variants of Rett syndrome have been described. In 1985, Hanefeld described a variant with the early appearance of convulsions. In this variant, the normal perinatal period is soon followed by the appearance of seizures, usually infantile spasms. We have observed two patients with signs of Rett syndrome showing acquired microcephaly and stereotypic midline hand movements. The disease started with generalised convulsions and myoclonic fits at 1.5 months in the first patient and with spasms at 10 days in the other, suggesting a diagnosis of the Hanefeld variant. In these patients, MECP2 point mutations and gross rearrangements were excluded by denaturing high performance liquid chromatography and real time quantitative PCR. The ARX and CDKL5 genes have been associated with West syndrome (infantile spasms, hypsarrhythmia, and mental retardation). Methods: Based on the clinical overlap between the Hanefeld variant and West syndrome, we analysed ARX and CDKL5 in the two girls. Results: We found frameshift deletions in CDKL5 in both patients; one in exon 5 (c.163_166delGAAA) and the other in exon 18 (c.2635_2636delCT). CDKL5 was then analysed in 19 classic Rett and 15 preserved speech variant patients, all MECP2 negative, but no mutations were found. Conclusion: Our results show that CDKL5 is responsible for a rare variant of Rett syndrome characterised by early development of convulsions, usually of the spasm type.